Positive Organizational Behavior in the Workplace - Youssef, Carolyn M.; Luthans, Fred (Journal of Management, 2007)
Drawing from the foundation of positive psychology and the recently emerging positive organizational behavior, two studies (N = 1,032 and N = 232) test hypotheses on the impact that the selected positive psychological resource capacities of hope, optimism, and resilience have on desired work-related employee outcomes. These outcomes include performance (self-reported in Study 1 and organizational performance appraisals in Study 2), job satisfaction, work happiness, and organizational commitment. The findings generally support that employees' positive psychological resource capacities relate to, and contribute unique variance to, the outcomes. However, hope, and, to a lesser extent, optimism and resilience, do differentially contribute to the various outcomes. Utility analysis supports the practical implications of the study results.